Interventions to reduce HIV-related stigma in the healthcare settings: a scoping systematic review - Che Ishak, Natalia; Kadir @ Shahar, Hayati; Abdul Manaf, Rosliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
HIV-related stigma will discourage the efforts in preventing new infections and engaging people to receive treatment, care and support programmes. Identifying the valuable interventions programmes to reduce HIV-related stigma in a healthcare setting is vital in order to deliver the best health services. A scoping systematic review was conducted. Articles were searched based on Pubmed and ScienceDirect search engines. The key words used were HIV stigma, intervention and healthcare. Published English articles in the past ten years involving HIV stigma intervention studies, and studies that involved healthcare workers in a healthcare setting were included. Reviewed articles, systematic review and meta-analysis articles were excluded. Primary screening of titles and abstract of 85 articles were done. Secondary screening of 19 articles resulted in 8 articles, included in this manuscript. Most of the reviewed articles showed, application of the Integrated Theoretical Model in the intervention programme as a guide and utilising combined intervention components are effective tools in delivering the intervention programme. The stigma reduction-intervention programme should focus on the intervention components as a whole including training of HCW, role plays, group discussions, games, sharing of information and contacts with PLHIV as well presentations and lectures. An integrative model of behavioural prophecy is perceived and it is particularly essential for interventions that focus on creating and fortifying the aim in conducting the chosen behaviour.